Pengembangan Permainan Edukasi berbasis Augmented Reality untuk Pembelajaran Senyawa Hidrokarbon bagi Siswa Sekolah Menengah Atas (SMA) - Carlista Naba; Muhammad Aminul Akbar; Ahmad Afif Supianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Chemistry is one of the many branches of science that is taught on high school, but observations from teachers shows that there's still many students who struggles learning chemistry because of its abstract and intangible concept. Example of a chapter that student still struggles is hydrocarbon chapter. To help with the problem of the abstractness concept of chemistry, this study has a goal to develop an educational game as a learning media to study about the structural molecule of hydrocarbon compound and its The International Union of Pure and Applied Chemistry (IUPAC) nomenclature using Augmented Reality (AR). The game will be developed as a puzzle game, on which the player arrange and build a hydrocarbon compound that can be seen on the real world with AR. The game will also detects the compound's name. This study will be done with Iterative Rapid Prototyping design cycle. The study's functionality result will be tested with Black Box Testing and tested on students with Game Experience Questionnaire (GEQ) module to asses the student's experience. There is 2 modules, which will be asked when the respondent is in their playing session, and when they're finished playing the game accordingly. The results of functionality testing shows that the game works well with 100% validity, just as the experience testing with GEQ. Based on the questionnaire results, game that uses AR could improve the student's interest and help them to overcome their feeling of boredom in learning.